2002
DOI: 10.1081/jas-120000804
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-stage asthma Screening Procedure for Elementary School Children†

Abstract: This paper describes an asthma screening procedure developed to identify children with asthma for an intervention study. Students were classified into three categories based on questionnaire responses (previous asthma, suspected asthma, and no evidence of asthma). Those classified as suspected asthma by questionnaire underwent further testing including spirometry and exercise challenge. Using the questionnaire alone, the measured asthma prevalence was 32%; the addition of spirometry and step testing reduced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…All newly identified children with asthma aged [7][8][9][10][11] years and their parents were involved in HRQOL study. A disease-specific quality-oflife questionnaire was used for the children and a generic questionnaire for parents.…”
Section: Methodsmentioning
confidence: 99%
“…All newly identified children with asthma aged [7][8][9][10][11] years and their parents were involved in HRQOL study. A disease-specific quality-oflife questionnaire was used for the children and a generic questionnaire for parents.…”
Section: Methodsmentioning
confidence: 99%
“…18 Previous response and participation rates indicated that the current population would yield 215 students classified as positive for asthma and 2561 students classified as negative for asthma. Assuming that no more than 25% of the 215 students classified as positive for asthma and no more than 10% of a stratified random sample of 240 of the 2561 no-asthma students were misclassified, we would estimate the sensitivity of the procedure with a 95% confidence interval (margin of error no greater than .032) for the best case (sensitivity: Ն95%) or 0.072 for the worst case (sensitivity: 50%).…”
Section: Sample-size Calculationsmentioning
confidence: 99%
“…Therefore, we developed and used a multistage procedure with questionnaires, spirometry, and exercise testing. 18,24 This article reports on a study designed to determine the validity of the University of Alabama at Birmingham (UAB) multistage case-detection procedure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interpretation was based on reference values established by Dockery and Hsu [17,18]. The submaximal exercise challenge step test was completed according to the protocol described by Gerald et al [19,20]. Briefly, the child stepped up and down on a single step maintaining a heart rate between 150-200 beats per minute for five minutes.…”
Section: Clinical Assessmentmentioning
confidence: 99%